Between challenges and opportunities: Traceability as a key to sustainable livestock farming in Colombia - Sandoval, Danny; Díaz, Manuel; Burkart, Stefan (2025)
Sustainable livestock farming has become a key pillar for the development of the livestock sector, particularly in the current context of global warming and climate change. In this scenario, countries must advance concrete adaptation and mitigation actions to reduce the negative impacts of livestock activities while improving competitiveness and sustainability. One of the critical tools to achieve these objectives is the implementation of traceability systems, which allow for the monitoring, tracking, and control of livestock activities across territories. In Colombia, traceability remains one of the main challenges in public policy for sector sustainability. Despite broad recognition of its importance, the lack of clear legislation and a coordinated national strategy has limited the effective development and implementation of these systems. Currently, there are several traceability initiatives promoted mainly by private actors on a small scale; however, they have not yet been scaled up or consolidated into a comprehensive national strategy. This study used a mixed-methods approach, beginning with a literature review on the current state of livestock traceability in Colombia. This was complemented by 20 interviews with key informants, including experts from public and private institutions involved in various traceability initiatives developed over the past 20 years. The aim was to capture key perspectives and practical experiences to better understand existing challenges and the specific needs a national traceability system must address. Results show that, despite successful experiences, significant barriers persist, including the absence of a centralised information and monitoring system, weak institutional capacity for intersectoral coordination, and the lack of standardised technical criteria for traceability and sustainability. Moreover, there is limited state capacity to integrate public and private efforts, essential for traceability to function as a value chain improvement mechanism, rather than solely as a tool for controlling deforestation or animal health. The study highlights the need to conceive traceability systems as comprehensive tools, integrating social, environmental, and economic information from producers to consumers. It also underscores the importance of continuous research to adjust strategies and strengthen decision-making processes in contexts where coordinating sustainability criteria among diverse actors remains particularly complex.